A method of measuring the neutron energy spectrum by activation detectors. (August 2016) - Wojciechowski, A.; Lim, Y.C.; Stepanenko, V.; Tiutiunnikov, S.; Khilmanovich, A.; Martsynkevich, B.
Highlights: Influence of experimental errors and uncertainty of cross sections on output errors. Explanation how to avoid disturbing final results by experimental errors. Calculation the neutron flux using experimental data from activation detectors. Experimental data of activation detectors from the KWINTA experiment in JINR, Dubna. Comparison of results based on experimental data with results from code MCNPX 2.7. Abstract: This work is a preliminary step toward the study of physical properties of the ADS systems, in which a deeply subcritical active core is irradiated by a pulsed beam of relativistic deuterons. This work analyzes a general direct method of calculating a neutron energy spectrum using efficiency of reactions of activation detectors. Our interest was focused on the study of the influence of input experimental errors and uncertainty of cross sections on output errors. The experimental data are taken from the KWINTA experiment in JINR, Dubna. The obtained results of the neutron flux spectrum in range 0.7–200 MeV are compared with calculation results from the MCNPX code.